Seasonal erosion and restoration of the dust cover on comet 67P/Churyumov-Gerasimenko as observed by OSIRIS onboard Rosetta - Hu, X.; Shi, X.; Sierks, H.; Fulle, M.; Blum, J.; Keller, H. U.; Kührt, Ekkehard; Davidsson, B. J. R.; Güttler, C.; Gundlach, B.; Pajola, M.; Bodewits, D.; et al. (Astronomy & Astrophysics, 2017)
Context: Dust deposits or dust cover are a prevalent morphology in the northern hemi-nucleus of comet 67P/Churyumov-Gerasimenko (67P). The evolution of the dust deposits was captured by the OSIRIS camera system onboard the Rosetta spacecraft having escorted the comet for over two years. The observations shed light on the fundamental role of cometary activity in shaping and transforming the surface morphology. Aims. We aim to present OSIRIS observations of surface changes over the dust deposits before and after perihelion. The distribution of changes and a timeline of their occurrence are provided. We perform a data analysis to quantify the surface changes and investigate their correlation to water activity from the dust deposits.We further discuss how the results of our investigation are related to other findings from the Rosetta mission. Methods. Surface changes were detected via systematic comparison of images, and quantified using shape-from-shading technique. Thermal models were applied to estimate the erosion of water ice in response to the increasing insolation over the areas where surface changes occurred. Modeling results were used for the interpretation of the observed surface changes. Results. Surface changes discussed here were concentrated at mid-latitudes, between about 20°N and 40°N, marking a global transition from the dust-covered to rugged terrains. The changes were distributed in open areas exposed to ample solar illumination and likely subject to enhanced surface erosion before perihelion. The occurrence of changes followed the southward migration of the sub-solar point across the latitudes of their distribution. The erosion at locations of most changes was at least about 0:5 m, but most likely did not exceed several meters. The erosive features before perihelion had given way to a fresh, smooth cover of dust deposits after perihelion, suggesting that the dust deposits had been globally restored by at least about 1 m with ejecta from the intensely illuminated southern hemi-nucleus around perihelion, when the north was inactive during polar night. Conclusions. The erosion and restoration of the northern dust deposits are morphological expressions of seasonality on 67P. Based on observations and thermal modeling results, it is inferred that the dust deposits contained a few percent of water ice in mass on average. Local inhomogeneity in water abundance at spatial scales below tens of meters is likely. We suspect that dust ejected from the deposits may not have escaped the comet in bulk. That is, at least half of the ejected mass was afloat in the inner-coma or/and redeposited over other areas of the nucleus.